Do personality traits predict outcome of psychodynamically oriented psychosomatic inpatient treatment beyond initial symptoms?. (22nd August 2014) - Steinert, Christiane; Klein, Susanne; Leweke, Frank; Leichsenring, Falk
<x xml:space="preserve">Abstract</x> Objectives Whether personality characteristics have an impact on treatment outcome is an important question in psychotherapy research. One of the most common approaches for the description of personality is the five‐factor model of personality. Only few studies investigated whether patient personality as measured with the NEO–Five‐Factor Inventory (NEO‐FFI, Costa & McCrae [1992b]. Revised NEO‐PI‐R and NEO‐FFI. Professional manual. Odessa, FL: Psychological Assessment Recources) predicts outcome. Results were inconsistent. Studies reporting personality to be predictive of outcome did not control for baseline symptoms, while studies controlling initial symptoms could not support these findings. We hypothesized that after taking into account baseline symptoms, the NEO‐FFI would not predict outcome and tested this in a large sample of inpatients at a psychosomatic clinic. Design Naturalistic, non‐controlled study using patients' data for multiple regression analysis to identify predictors of outcome. Methods Data of 254 inpatients suffering primarily from depressive, anxiety, stress, and somatoform disorders were analysed. Personality was assessed at the beginning of therapy. For psychotherapy outcome, changes in anxiety and depression (Hospital Anxiety and Depression Scale; HADS), overall psychopathology (Symptom Checklist‐90‐R Global Severity Index [GSI]), and interpersonal problems (Inventory of Interpersonal Problems; IIP) were measured. Results The treatment resulted in significant decreases on all outcome measures corresponding to moderate to large effect sizes (HADS: d = 1.03; GSI: d = 0.90; IIP: d = 0.38). Consistent with our hypothesis, none of the personality domains predicted outcome when baseline symptoms were controlled for. Conclusions Personality assessment at baseline does not seem to have an added value in the prediction of inpatient psychotherapy outcome beyond initial symptoms. Practitioner points Clinical implications Personality dimensions overlap with symptomatic distress. Rather than serve as predictors of outcome, the domains tapped by the NEO‐FFI reflect current psychological symptomatology in inpatients with depressive, anxiety, stress or somatoform disorders. From a clinician's point of view monitoring individual progress by using actuarial measures is more valuable than trying to predict who will benefit from treatment using personality assessments. Limitations of the study Diagnostic assessment was solely based on clinical evaluation rather than structured interviews. Twenty‐five per cent of the original sample had to be excluded due to missing data. There was a focus on only one set of client characteristics (i.e., five‐factor model personality traits). Assessment of personality domains in the acute phase of a mental disorder may be problematic and could have influenced findings.